THE IMPACT OF HEALTHCARE ADMINISTRATION DIGITALIZATION ON HOSPITAL SERVICE EFFICIENCY WITH HEALTHCARE WORKER SATISFACTION AS A MEDIATING VARIABLE - Eko Supryanto Raja Lado; Vip Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study reviews the literature to examine the impact of healthcare administration digitalization on hospital service efficiency, with particular attention to the mediating role of healthcare worker satisfaction. Findings reveal that digitalization enhances efficiency through improved data accuracy, reduced administrative burden, optimized resource allocation, and better interdepartmental coordination. However, these benefits are not automatic; they are strongly mediated by the satisfaction of healthcare workers, who determine the level of adoption, utilization, and sustainability of digital systems. When digitalization initiatives are accompanied by adequate training, managerial support, and user-friendly system design, healthcare worker satisfaction increases, which in turn reinforces engagement, reduces turnover, and strengthens organizational efficiency. Conversely, poorly implemented systems may create dissatisfaction, stress, and new inefficiencies. This highlights the need for hospitals to adopt a holistic approach to digital transformation that balances technological innovation with human resource development. The review concludes that healthcare worker satisfaction is a pivotal mechanism linking digitalization and efficiency, and its integration into hospital management strategies is critical for achieving sustainable improvements in healthcare delivery.